Can Virtual Reality Training Effectively Improve Physical Condition and Back-Row Attack in Volleyball? - Bujang Bujang; Yusuf Hidayat; Mia Kusumawati; Hasan Basri; Azi Faiz Ridho; Wahidah Tumijan; Wan Ahmad Munsif Wan Pa; Dywa Ikal Mutaqin; Bimo Subagyo (Journal of Coaching and Sports Science, 2025)
Background: There is an urgent need to explore innovative training methods that can improve the physical condition and back-row attack performance of junior volleyball players. Despite its great potential, Virtual Reality (VR) is still underutilized in youth sports training.Aims: This study aims to test the effectiveness of VR-based training in improving physical conditioning and back-row attack quality.Method: A quasi-experimental design was employed with 24 junior volleyball athletes aged 14 to 16. The participants underwent VR-based training three times a week for six weeks, with each 45-minute session consisting of a 15-minute warm-up, a 30-minute training session, and a 5-minute cool-down. Measurement tools included vertical jump tests, 20-meter sprints, Illinois agility tests, and structured observations to evaluate physical performance and back-row attack effectiveness. Data were analyzed using paired t-tests and multiple linear regression.Result: The results showed significant improvements in vertical jump height (d = −8.18), sprint time (d = 2.42), agility score (d = 3.32), and back row attack (d = −3.32) at p < 0.001. Structured observations revealed improvements in the accuracy, timing, and coordination of back-row attacks. Regression analysis revealed that a better physical condition, particularly in terms of jumping and agility, significantly contributed to improved back-row attack performance (R² = 0.876, p < 0.001).Conclusion: These findings suggest that VR-based training can effectively enhance physical condition and technical performance in back-row attacks, likely due to the immersive simulation environment supporting enhanced motor learning and situational awareness.